Teacher training forCLIL in Higher Education: challenges in blended learning - Moreira Silva, Manuel (2017)
Researchers and foreign language teachers of ReCLes.pt (the Network Association of Language Centers in Higher Education in Portugal) would like to share recent research on a blended learning format for teacher training for CLIL (Content and Language Integrated Learning), based on a course carried out in the 2nd semester of 2016/2017 for teachers at four geographically disperse polytechnic instituts in Portugal. The course was implemented in these four different educational environments and had as trainees teachers of other subjects, representing specialty areas such as Experimental and Exact Sciences, Technology, Engineering, and Management. Together, the trainers from each of the four schools designed and carried out the teacher training, online and in loco, with initial face-to-face (F2F) sessions to establish a community of practice and a common objective – to learn to create conditions for learning that simultaneously promote the proposed subject and the foreign language through which it is taught. The framework of the b-learning course is the widely-used CLIL Training Guide (Morgado et al. 2015), available at http://recles.pt/, which includes techniques for scaffolding to build new concepts upon previously acquired competences and terminologically-inspired approaches and instruments for acquiring the much-needed specialist terminology of each subject. Also covered are the principles of how to teach effectively through English, activating and consolidating linguistic competences, considering aspects of classroom management and student learning styles. The assynchronous and F2F sessions also consisted of individual orientation and tutorial work with the teacher trainees, followed by classroom observation of the resulting CLIL module and interviews with the students and the teacher trainees. By ensuring the best possible application of the teachers’ new teaching competences, we aim to better understand just how students in higher education are receiving this new approach to learning through a foreign language. Overall, the present experience will serve for further national and international editions of this valuable opportunity to be trained in CLIL for higher education as it has allowed for reflection on the potential and the challenges for blended learning – ranging from the cohesion, distribution, and relevance of the topics covered to management of time for executing the assignments and to issues related to personal learning spaces. Learner satisfaction (for the teacher trainers and the students of these higher education CLIL modules) is high although realistic expectations about time are a consistent difficulty to be negotiated.